2006
DOI: 10.1038/sj.jes.7500522
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of short-term residential measurement in the prediction of 72-h exposure to power frequency magnetic field in households very close to high-tension transmission lines

Abstract: , a total of 80 single-dwelling households close (o70 m) to high-tension (161 or 345 kV) power lines in a northern community of Taiwan received measurements of indoor extremely low-frequency (ELF) magnetic field for 72 h. Measurements were performed with EMDEX IIt meter at a sampling rate of every 300 s, yielding some 860 readings of ELF magnetic field for each household. In addition to the 72-h mean ELF magnetic field, we also calculated arithmetic means of the first 2, 6, 12, and 288 readings taken in each h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…Second, our data showed that 87% of urban residences were located in apartment buildings while only 18% of residences were apartments in the rural sample. Two previous studies reported an association between residential characteristics and indoor ELF-MF where residences of apartment buildings were likely to have higher ELF-MF exposure than single-dwelling houses [Clinard et al, 1999;Ger et al, 2006]. This study presented no significant urban rural differences in residential measures of ELF-MF, which may be largely due to the household appliances and utilities not having much variation among general population in Taiwan.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Second, our data showed that 87% of urban residences were located in apartment buildings while only 18% of residences were apartments in the rural sample. Two previous studies reported an association between residential characteristics and indoor ELF-MF where residences of apartment buildings were likely to have higher ELF-MF exposure than single-dwelling houses [Clinard et al, 1999;Ger et al, 2006]. This study presented no significant urban rural differences in residential measures of ELF-MF, which may be largely due to the household appliances and utilities not having much variation among general population in Taiwan.…”
Section: Discussioncontrasting
confidence: 54%
“…Although we noted that the proportion of residences with ELF-MF higher than 0.3 or 0.4 mT was also higher in urban residences, such differences reached no statistical significance mainly due to a small number of residences with high exposure in our sample. Findings from previous studies showed an apparent geographic variation in residential ELF-MF in which urban residences tended to have higher levels of indoor ELF-MF [Li et al, 1997;Clinard et al, 1999;Ger et al, 2006]. A number of factors could contribute to such urban rural differences in ELF-MF exposure level.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We are not surprised to note higher ELF-MF exposure (including mean and 25th, 50th and 75th percentiles) in those campuses in such close proximity to high-voltage power lines, since other studies have reported similar findings; indeed the increase has been found to be as high as 6.0 mT [Ger et al, 2007].…”
Section: Discussionmentioning
confidence: 52%
“…However, distance from the dwelling to a powerline is neither a sufficient proxy for residential exposure to ELF MF (Ger et al, 2007;Maslanyj et al, 2009), nor for 24 h' exposure. Therefore, in this study we further explored the association between NSPS and exposure to ELF MF as determined by a 24 h' personal measurement using exposimeters.…”
Section: Introductionmentioning
confidence: 98%